DLR's Mobile Rocket Base - Flight Tickets For Your Microgravity Experiments - Stamminger, Andreas; Altenbuchner, Ludwig; Ettl, Josef; Hörschgen-Eggers, Marcus; Jung, Wolfgang; Turner, Peter (2013)
Mobile Rocket Base (MORABA), a section of DLR’s Space Operations and Astronaut Training Department fosters the national and international scientific community to prepare and implement sounding rocket and balloon borne experiments in the fields of aeronomy, astronomy, geophysics, hypersonic and especially microgravity research worldwide. In addition, satellite missions can be supported by mobile tracking radars for trajectory determination as well as with TT&C ground stations. MORABA also supplies a number of mechanical and electrical flight systems for use on rockets, balloons and short duration satellite missions. During the last four decades more than 200 campaigns have been performed in Antarctica, Australia, Brazil, France, Greenland, India, Italy, Japan, Norway, Spain, Sweden and USA. Depending on the scientific aim, an appropriate launch range is selected and complemented or fully equipped with MORABA’s mobile infrastructure, such as launcher, telemetry and tracking stations. Converted military or commercial launch vehicles, as well as all necessary mechanical and electrical subsystems are supplied by MORABA. For the launch of rockets, stability and performance calculations are carried out to ensure correct vehicle performance and to meet range safety aspects. This paper will give an overview of the MORABA infrastructure for sounding rocket missions and it will focus on flight tickets for experiments that require perfect microgravity conditions. It will give also a survey of projects with MORABA involvement of the last two years and the next two years.